EMEVÎ İDARESİNDE KABİLECİLİĞİN ROLÜ VE ÖNEMİ - BOZMAZ, FATİH (Fırat Üniveristesi, 2021)
İslâmiyet öncesi dönemde Hz. Peygamber'in (a.s) atası olan Hâşim ile Ümeyyeoğullarının ataları arasında çekişme vardı. Arap kültüründe çok önemli bir yeri olan kabilecilik duyguları ile bu çekişme kendisini uzun bir süre devam ettirdi. Hz. Peygamber İslâm tebliğine başladığında Haşimoğullarının bu yükselişi Ümeyyeoğullarını rahatsız etti. Ümeyyeoğulları Hazreti Peygamberin Mekke'yi fethine kadar bu kabileci dürtülerle İslâm'ın en büyük düşmanı oldular. Mekke'nin fethi ile artık Müslüman olan Ümeyyeoğulları na Hazreti Peygamber önemli görevler verdi. İlk iki halife döneminde sessizliğini koruyan bu kabile, akrabaları olan Hazreti Osman'ın hilafeti döneminde oldukça güçlendiler. Hz. Ali döneminde Haşimoğulları ile Ümeyyeoğulları tekrar karşı karşıya geldi. Neticede Muaviye'nin liderliğindeki Ümeyyeoğulları Haşimoğullarına galip gelerek Emevî Devleti resmen kuruldu. Emeviler Devleti'nin gücü büyük oranda Şam'daki Güneyli kabileler alan Yemenî Kelb kabilesine dayanıyordu. Bu durum Kuzeyli kabilelerin tepkisine neden oluyordu. Emevî halifeleri bazıları kabileler arası dengeye önem verirken bazıları ise sadece bir kabileyi tutup diğer kabileyi dışlıyordu. Kabile çekişmeleri nedeniyle Yemenî kabilelerinin Emevîlerden desteğini çekmesiyle Abbasiler Emevîleri kolayca yıktı.

In the pre-Islamic period, there was a conflict between Hashims, the ancestor of the Hz. Mohammed (a.s), and the ancestors of the Umayyads. This conflict with the feelings of tribalism, which has a very important place in Arab culture, continued for a long time. When the Hz. Mohammed (a.s) started to preach Islam, this rise of the Hashimites disturbed the Umayyads. The Umayyads became the greatest enemies of Islam with these tribal impulses until the Prophet's conquest of Mecca. With the conquest of Mecca, the Prophet gave important duties to the Umayyads, who became Muslims. This tribe, which kept its silence during the first two caliphs, gained strength during the caliphate of their relatives, Hz. Osman. During the Hz. Ali period, Hashims and Umayyads came face to face again. As a result, the Umeyyeds under the leadership of Muaviye defeated the Hashims and the Umayyad State was officially established. The power of the Umayyad State was largely based on the Yemeni Kelb tribe, which received Southern tribes in Damascus. This caused the reaction of the Northern tribes. Some of the Umayyad caliphs gave importance to the balance between the tribes, while others kept only one tribe and excluded the other tribe. As the Yemeni tribes withdrew their support from the Umayyads due to tribal conflicts, the Abbasids easily overthrew the Umayyads.
The role and importance of tribalism in the Umayyad administration
Keywords: Tarih